SIMOSA: Design and Implementation of a Waste Monitoring Application for Integrated Urban Waste Management - Zhafran Rafi Al Rasyid; M. Said Hasibuan (Penerbit Goodwood, 2024)
Purpose: Urban waste accumulation poses a persistent environmental governance challenge across Indonesian cities, driven by rapid population growth, insufficient collection infrastructure, and the absence of demand-responsive coordination mechanisms linking waste generators to available collection services.Methodology: This study applies the Prototype development methodology to design and implement Sistem Monitoring Sampah (SIMOSA), an Android-based mobile application developed using Android Studio with Java, Firebase Authentication and Realtime Database, and Google Maps SDK. Development stages encompassed problem identification, data collection through observation and interviews, stakeholder communication, quick planning, interface modeling, prototype construction, and Black Box functional testing.Results: SIMOSA was successfully implemented as a dual-role Android application supporting Customer (waste generator) and Driver (waste collector) roles within a single installation. Black Box testing confirmed 100% pass rates across all six core features: Login, Registration, Menu Selection, Map/Pickup Location Input, Driver Matching, and Order Completion. Conclusions: SIMOSA provides a functional, accessible technological solution for urban waste pickup coordination, reducing informal disposal by enabling on-demand requests through a straightforward mobile interface with Google Maps and Firebase real-time synchronization.Limitations: The application is currently limited to Android; iOS deployment is absent. Real-time driver location tracking during transit is incomplete, and formal security penetration testing has not been conducted.Contributions: SIMOSA contributes a replicable Android, Firebase, and Google Maps architecture for community-level waste pickup coordination adaptable to diverse urban waste management contexts across Indonesian cities.